The immune response in tubercular uveitis and its implications for treatment: from anti-tubercular treatment to host-directed therapies - Putera, Ikhwanuliman (2024)
Tubercular uveitis (TB-uveitis) remains a conundrum in the uveitis field, which is mainly related to the diverse clinical phenotypes of TB-uveitis. Moreover, it remains difficult to differentiate whether Mycobacterium tuberculosis (Mtb) is present in the ocular tissues, elicits a heightened immune response without Mtb invasion in ocular tissues, or even induces an anti-retinal autoimmune response. Gaps in the immuno-pathological knowledge of TB-uveitis likely delay timely diagnosis and appropriate management. In the last decade, the immunopathophysiology of TB-uveitis and its clinical management, including experts' consensus to treat or not to treat certain conditions with anti-tubercular treatment (ATT), have been extensively investigated. In the meantime, research on TB treatment, in general, is shifting more toward host-directed therapies (HDT). Given the complexities of the host-Mtb interaction, enhancement of the host immune response is expected to boost the effectiveness of ATT and help overcome the rising burden of drug-resistant Mtb strains in the population. This review will summarize the current knowledge on the immunopathophysiology of TB-uveitis and recent advances in treatment modalities and outcomes of TB-uveitis, capturing results gathered from high- and low-burden TB countries with ATT as the mainstay of treatment. Moreover, we outline the recent progress of HDT development in the pulmonary TB field and discuss the possibility of its applicability to TB-uveitis. The concept of HDT might help direct future development of efficacious therapy for TB-uveitis, although more in-depth research on the immunoregulation of this disease is still necessary.